Situational Theory of Problem Solving (STOPS) and Radio (RIPS) as Joint Concept on Farmers Response Towards Insufficient Information Delivery - Idris Ismail (Universiti Sains Islam Malaysia, 2024)
Insufficient information delivery has been identified as an Agricultural Extension Services (AES) situational problem. As this problem continues to bother farmers within the AES situation persistently, many developing countries are still found struggling with this situational problem. Although research have been conducted to address this problem. However, were still particularly to close the gap in the diffusion of information and technology acceptance focusing on production. It is clear that efforts to report on farmers’ actual perception and reaction in terms of how they accept and react towards the problem have not been sufficiently investigated. Taking a communication perspective, the Situational Theory of Problem Solving (STOPS) anchored the argument on Malaysian farmers’ response towards insufficient information delivery. This study aims to identify the segmentation of farmers on the problem, understand the farmers’ perceptual situation, motivation and communicative action towards solving this problem, and whether Radio in Problem Solving (RIPS) influences the farmers’ response towards insufficient information delivery. A predominantly quantitative, explanatory research design was assigned. A total of 400 farmers within the AES “Rice Bowl” area of Northern Malaysia had participated in the questionnaire and seven individual interviews were subsequently conducted. The quantitative data were analysed using Structural Equation Modelling (SEM), while content analysis was used to analyse the interview data. The quantitative findings revealed that all the nine hypothesised relationships proposed in the research’s conceptual model were significant and supported. Additionally, results from the qualitative analysis were consistent and supported the quantitative findings. Four types of public were found with the active public being the dominant group in this study. While the original proposition of STOPS provided good information on the farmers’ response towards insufficient information delivery, RIPS was also able to influence farmers perceived situation as problematic and thus efforts are needed to solve it. RIPS seems to have an influence on the farmers’ problem recognition and involvement recognition, apart from reducing their constraint as well as motivated them in solving the problem. Understanding the farmers’ perception, motivation and communicative action bring a positive approach to the field of public relations, particularly through STOPS and RIPS as newly introduced concepts which contribute to solve the insufficient information delivery problem in AES. Thus, enabling AES to reinforce farmers’ upward behavioural approach that allows them to invest their ability on the problem which could be made routine and as part of the AES’ information delivery strategy.